Effectiveness of Disease Control Measures on the Transmission Risk of SAR-Cov-2 among High-Risk Contacts: a Case Study in Phuket, Thailand - เสริมแก้ว , ธนิศ; สังข์แก้ว, ณิชาพัชร; ภู่เจริญ, ชยานนท (Journal of Health Science of Thailand, 2021)
During the first wave of COVID-19 (April- May 2020), Phuket had the second-largest accumulated number of COVID-19 confirmed cases nationwide. Two major stringent disease control measures, including complete quarantine of all high-risk contact (HRCs) in stated provide facilities (LQ) and district lockdown, were implemented. This paper analyzes the effectiveness of those two policies by employing the Probit model to assess the infection probability of high-risk contact during policy implementation. The results indicated that a complete quarantine of all high-risk contacts in LQ significantly alleviated their infection probability as the household secondary attack rate among HRCs statistically diminished after this measure had been implemented. We found no evidence that the implementation of district lockdown could statistically reduce the infection probability of all HRCs in our samples. However, an increase in household transmission’s coefficient among high-risk contact was found instead when this policy was annexed. Hence, the district lockdown policy should be implemented with full caution.